Strong Exponential Attractors for Weakly Damped Semilinear Wave Equations - Cuncai Liu; Fengjuan Meng; Chang Zhang (Journal of Mathematics)
In this paper, we investigate the longtime dynamics for the damped wave equation in a bounded smooth domain of ℝ3. The exponential attractor is investigated in a strong energy space for the case of subquintic nonlinearity, which is based on the recent extension of the Strichartz estimate for the case of a bounded domain. The results obtained complete some previous works.